Hubungan Dukungan Suami dan Umur Akseptor KB Dengan Pemakaian Metode Kontrasepsi IUD - Harahap, Yanna Wari; Hairani, Nikma; Dewi, Sri Sartika Sari (Jurnal Kesehatan Ilmiah Aufa Royhan, 2019)
IUD is one of the contraceptive methods that has high effectiveness. The prevalence of the use of active contraception in Indonesia is 63.22% with the use of IUD contraception is 7.15%, injections 62.77% and pills 17.24%, in Padangsidimpuan city use of IUD contraception is 8.5%, injections 42.2% and pills 20.6%, in sihitang village use of IUD contraception is 5.19%, injections 56.73% and pills 13.84%. In this data use of IUD contraception is still very low. The low use of IUD is due to several factors, including age and husband support. This research analyzes the relationship between husband support and family planning acceptor age by using the IUD contraceptive method in Sihitang Village of Southeast Padangsidimpuan subdistrict Padangsidimpuan City 2019. This type of research is analytic survey with cross sectional design. The population in this study amounted to 527 active family planning acceptor and sample of 84 people were taken by simple random sampling technique. The instrument of this study is a questionnaire, with the analysis carried out namely univariate and bivariate(α = 95%). The results of the analysis found that the majority of husband support variables did not support (54.8%) and the majority of the age of> 35 years (60.7%). Based on the results of the chi-square test obtained the relationship of husband support with the use of the IUD contraceptive method (p-value = 0.054) and the age variable is not related to the use of the IUD contraceptive method (p-value = 0.350> 0.1). The low use of IUD in this study was due to the high proportion of mothers who did not have the support of their husbands. It is expected that the husband will play an active role in providing support or participation with his wife in attending counseling about the use of contraceptive methods.